Juvenile justice Care and protection of children Act 2000 - Nizam Azeez Sait (LexisNexis, 2014)
This book provides a clear overview of the Juvenile Justice system in India. It explains simply and concisely all the critical facets of this most important part of justice administration in the country: • The relevance of the Constitutional mandate • The provisions of the Juvenile Justice (Care and Protection of Children) Act, 2000 as amended with salient features lucidly set out • Comprehensive case law arranged section-wise with pertinent topical headings • Relevant international covenants and the role of the United Nations in the development of JJ regime • The history of the law in India and the reasons for the radical changes in it • The significance of adoption for successful rehabilitation and reintegration into society of juveniles in need of care • Supreme Court guidelines highlighted and examined This handy volume will prove indispensable to legal practitioners, trial judges, NGOs working on schemes for juveniles, child rights activists. It will also be of interest to a wider readership including journalists and social scientists.